Development of hydroimpulsive rock failure device in rotary percussion drilling; Проблемы геологии и освоения недр; Т. 2 - Fedin D. V. Dmitry Vladimirovich (Geology, mining and petroleum engineering (English, German), 2012)
Заглавие с титульного листа